Análise jurídica da teoria de Alf Ross - Andaku, Juliana Almenara (2005)
This paper analyzes Alf Ross´s thought (1899 1979), based in some of his works, specially the articles published in the book celebrating the centenary of his birthday, as well as the influence he suffered from Hägerström, Lundstedt and Olivecrona, also trying to study his work in the historical period which he had lived. The main idea of this paper is to study the law concept in Alf Ross´s thought. In some cases, it will be the way law is expressed and studied in Alf Ross´s works and how this subject is analyzed in his books and articles, trying to see if there were changes in the way he treated this subject in time and which were the influences he suffered this period (doctrinarian, historical or personal). In the first chapter we analyze the historical period he has lived and the changes that happened in his personal and professional life, to understand the way his thought was influenced by these facts. In the second chapter, we turn back to the sources of Alf Ross´s thought, studying the three Swedish jurists that preceded him in the Scandinavian Realism theory. In the third chapter, we make a bibliographic revision of Ross´s works, emphasizing his works in Danish. The objective of this research is to deep our knowledge of Alf Ross´s works, presented in his books and articles, some of them unpublished in Brazil. This paper tries to recover the essence of Alf Ross´s thought, analyzing thoroughly his works, as well as the doctrinarian and personal influences, to make possible to draw the largest prospect of his works.